2021
DOI: 10.3390/en14248604
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Injection Well Location on CO2 Geological Storage Efficiency

Abstract: An analysis of the influence of injection well location on CO2 storage efficiency was carried out for three well-known geological structures (traps) in deep aquifers of the Lower Jurassic Polish Lowlands. Geological models of the structures were used to simulate CO2 injection at fifty different injection well locations. A computer simulation showed that the dynamic CO2 storage capacity varies depending on the injection well location. It was found that the CO2 storage efficiency for structures with good reservo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…This coefficient varies widely from 4 to 20 kg of CO2 per 1 kg of crude oil. This result means a strong dependence on the effectiveness of the method used in the selection of the system of injecting wells [42], which differed in the individual Scenario III variations. This means that there exists a potential opportunity to optimize The basic results of the nine Scenarios of the field production in the forecast period from 2022 to 2042 are presented in Table 4.…”
Section: Time [Years]mentioning
confidence: 99%
“…This coefficient varies widely from 4 to 20 kg of CO2 per 1 kg of crude oil. This result means a strong dependence on the effectiveness of the method used in the selection of the system of injecting wells [42], which differed in the individual Scenario III variations. This means that there exists a potential opportunity to optimize The basic results of the nine Scenarios of the field production in the forecast period from 2022 to 2042 are presented in Table 4.…”
Section: Time [Years]mentioning
confidence: 99%
“…The Konary geological structure and the possibility of storing hydrogen and carbon dioxide are of interest to the authors [70][71][72]. The outline of the Konary structure model is presented in Figure 1.…”
Section: Geological Model Of the Konary Structure And Previous Researchmentioning
confidence: 99%
“…In addition, the location of the injection wells also affects the efficiency of storage. Luboń simulated the injection results of 50 wells. They found that the storage effect will be improved when the distance and depth difference between the injection well and the top of the structure increases for structures with good reservoir properties, but the opposite is true for structures with poor reservoir physical properties.…”
Section: Co2 Storagementioning
confidence: 99%